2015
DOI: 10.1016/j.desal.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-solvent additives on the morphology and separation performance of poly( m -phenylene isophthalamide) (PMIA) hollow fiber nanofiltration membrane

Abstract: • PMIA hollow fiber NF membranes were fabricated.• Effects of non-solvent additives on the morphology and separation performance were studied.• High content of non-solvent additives resulted in narrow pore size, pore size distribution and high rejection. Newly designed poly(m-phenylene isophthalamide) (PMIA) hollow fiber nanofiltration membranes were fabricated containing non-solvent additives, i.e., lithium chloride (LiCl), acetone and PVP by dry-jet wet spinning technology. The effects of non-solvent additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Pore forming agents (i. e. porogens), in particular, have been employed to manipulate phase inversion and control membrane porosity and increase selectivity of separation. Polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and LiCl are among more frequently used porogens known to affect the thermodynamic state of the casting mixture as well as conformation and dynamics of the polymers in the mixture [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…Pore forming agents (i. e. porogens), in particular, have been employed to manipulate phase inversion and control membrane porosity and increase selectivity of separation. Polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and LiCl are among more frequently used porogens known to affect the thermodynamic state of the casting mixture as well as conformation and dynamics of the polymers in the mixture [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…PMIA is a polymer with high performance such as good spinnability, high hydrophilicity, excellent mechanical properties, strong corrosion resistance, and superior performance at high temperature. Wang et al . prepared a novel PMIA hollow fiber nanofiltration membranes and found that by increasing the concentration of nonsolvent additives, the morphologies changed from finger‐like to sponge‐like, and the outer skin‐layer thickness was slightly increased.…”
Section: Introductionmentioning
confidence: 99%
“…; Wang et al . ), has been investigated to be added into the coagulation bath to control and modify morphological and physical characteristics of the membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Composition of the casting solution and the coagulation bath were found to be important key factors influencing the morphology and the performance of the prepared membranes (Wang et al 2003). Different additives such as lithium chloride (Wang et al 1999), lithium perchlorate (Wang et al 2003), ethanol , organic salts (Wang & Wang 2005;Wang et al 2014), has been investigated to be added into the coagulation bath to control and modify morphological and physical characteristics of the membranes.…”
Section: Introductionmentioning
confidence: 99%